Geografia da saúde em Anápolis (GO): aplicativo Mosquito Control como uma contribuição para o controle da Dengue - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The endemic problems arise due to the lack of control of theurban perimeter, which grows with the passing of the years, constituting obstacles to the publicadministration, generating consequent ills for the population. Today in Brazil dengue isconsidered a serious public health problem, given the alarming numbers of people affected by the disease caused by the mosquito Aedes aegypti. Data on occurrences of dengue have also beenfrequent in the city of Anapolis, where in 2016 the number of people infected with dengue was15,767. Such a scenario suggests the need to think about the geography of this disease, from itscausal factors to the proposition of instruments for its control. This study is based on thetheoretical approach of Health Geography, through which it is possible to think of the city as anenvironment formed by physical, social and economic elements, which may be associated with theissue of regional distribution of diseases. The general objective of this study is to analyze theGeography of Dengue in the city of Anapolis - GO between the years 2010 and 2018, besidescontributing with the issue of communication between the population and the health agents,presenting an application that allows the multiplication of information about fragile areas to vector proliferation. Data were collected on the number of dengue cases recorded by neighborhoods, together with the Municipal Health Department of Anapolis and EpidemiologicalSurveillance, which were spatialized, making it possible to identify the correlation between urbangrowth, infrastructure, public health and cases of dengue in the city between the years 2010 to2018. For construction of the application called Mosquito Control will be used Mapboxtechnology compatible with mobile devices. The construction of this application is in thedevelopment phase, completing the Requirements Analysis and consequent creation of thediagrams that support the phase in which it is currently.
Geography of health in Anapolis (GO): Mosquito Control App as a contribution to control Dengue
Keywords: Aedes aegypti; aplicativos móveis; Geotecnologias; Aedes aegypti; mobile apps; Geotechnologies; GEOGRAFIA HUMANA::GEOGRAFIA DA POPULACAO; CIENCIAS DA SAUDE::SAUDE COLETIVA; SAUDE COLETIVA::EPIDEMIOLOGIA